Perancangan Sistem Informasi Penilaian Siswa Berbasis Web Pada SMK Al-Husna Kota Tangerang - Padeli, Padeli; Ramadhan, Gilang Kartika Hanum; Aprilyani, Ulfa Tiana (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
Rapid technological developments in the current era of globalization have provided many benefits in progress in various aspects. Besides being used to process data and store computer data, it can also be used to support the application and utilization of information and communication technology. At this time in the Tangerang Al-Husna Vocational School the processing or scoring system of student grades has been running semi-computerized but is still limited by using Microsoft Excel. This will result if the student value data occurs unintentional changes will affect other data as well and can cause loss or problems in the student's assessment recorded and stored in a conventional way. The purpose of this research is to change the student assessment system which is currently running semi-computerized into a system that is fully computerized, namely a web-based system and can be accessed online so that the value processing of students does not take a long time and is expected to run effectively and efficiently. The method used to analyze the problems in the research is by using the SWOT method (Strength, Weakness, Opportunities, Threats) while for the system design method using UML (Unified Modeling Language) and for programming languages ​​using PHP and MYSQL in making the database. With the implementation of this website-based system, it is expected to facilitate the student assessment process that can be done quickly and accurately. Keywords: System, Assessment, Students